Paired Associative Stimulation Targeting the Tibialis Anterior Muscle using either Mono or Biphasic Transcranial Magnetic Stimulation - Mrachacz-Kersting, Natalie; Stevenson, Andrew J. T. (Frontiers in Human Neuroscience, 2017)
Paired associative stimulation (PAS) protocols induce plastic changes within the motor cortex. The objectives of this study were to investigate PAS effects targeting the tibialis anterior (TA) muscle using a biphasic transcranial magnetic stimulation (TMS) pulse form and, to determine whether a reduced intensity of this pulse would lead to significant changes as has been reported for hand muscles using a monophasic TMS pulse. Three interventions were investigated: (1) suprathreshold PAbi-PAS (n = 16); (2) suprathreshold PAmono-PAS (n = 11) where PAS was applied using a biphasic or monophasic pulse form at 120% resting motor threshold; (3) subthreshold PAbi-PAS (n = 10) where PAS was applied as for (1) at 95% active motor threshold. The peak-to-peak motor evoked potentials (MEPs) were quantified prior to, immediately following, and 30 minutes after the cessation of the intervention. TA MEP size increased significantly for all interventions immediately post (61% for suprathreshold PAbi-PAS, 83% for suprathreshold PAmono-PAS, 55% for subthreshold PAbi-PAS) and 30 min after the cessation of the intervention (123% for suprathreshold PAbi-PAS, 105% for suprathreshold PAmono-PAS, 80% for subthreshold PAbi-PAS. PAS using a biphasic pulse form at subthreshold intensities induces similar effects to conventional PAS.